2022
DOI: 10.3233/jad-215061
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Behavioral and Psychological Symptoms of Dementia (BPSD) and BPSD Sub-Syndromes in Early-Onset and Late-Onset Alzheimer’s Disease

Abstract: Background: Behavioral and psychological symptoms of dementia (BPSD) have a large impact on the quality of life of patients with Alzheimer’s disease (AD). Few studies have compared BPSD between early-onset (EOAD) and late-onset (LOAD) patients, finding conflicting results. Objective: The aims of this study were to: 1) characterize the presence, overall prevalence, and time of occurrence of BPSD in EOAD versus LOAD; 2) estimate the prevalence over time and severity of each BPSD in EOAD versus LOAD in three stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 67 publications
2
30
1
1
Order By: Relevance
“…Alzheimer's disease (AD) is the most widespread neurodegenerative disorder worldwide (20)(21)(22), typically characterized by memory loss and other cognitive deficits (20,23). BPSD are being increasingly recognized as common serious problems in AD (8). Several findings suggest that some BPSD-i.e., depression, anxiety, and apathy-can occur before the onset of cognitive decline in AD (8,24,25) and could predict both cognitive decline and progression from MCI to AD (26).…”
Section: Alzheimer's Disease (Ad) and Bpsdmentioning
confidence: 99%
See 1 more Smart Citation
“…Alzheimer's disease (AD) is the most widespread neurodegenerative disorder worldwide (20)(21)(22), typically characterized by memory loss and other cognitive deficits (20,23). BPSD are being increasingly recognized as common serious problems in AD (8). Several findings suggest that some BPSD-i.e., depression, anxiety, and apathy-can occur before the onset of cognitive decline in AD (8,24,25) and could predict both cognitive decline and progression from MCI to AD (26).…”
Section: Alzheimer's Disease (Ad) and Bpsdmentioning
confidence: 99%
“…The pathogenesis of these symptoms is not still completely understood, and the current knowledge supports multifactorial causes, involving the interaction of biological, psychological, and social factors (7). It has been shown that BPSD are associated with high levels of distress both in dementia sufferers and their caregivers, as well as with adverse outcomes, long-term hospitalization, and misuse of medications and increased use of health care resources (8)(9)(10)(11)(12). Thus, in addition to cognitive deterioration, BPSD are a relevant and meaningful clinical target for intervention (13) although are still now considered as non-disease-specific markers (14).…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer’s disease (AD) is the most frequent type of dementia in elderly people [ 1 ]. The clinical features of AD include both cognitive decline and a set of non-cognitive symptoms involving perception, mood, personality, and basic functioning, overall known as Neuropsychiatric or Behavioral and Psychological Symptoms of Dementia (BPSD) [ 2 , 3 ]. Two major forms of the disease exist: sporadic (SAD)—whose causes are not completely understood—and familial (FAD)—with a clear autosomal dominant inheritance [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, this study was aimed at identifying comparatively relevant biomarkers related to altered gene expression in the hippocampus and blood of the double transgenic AT mouse model. These mice express the mutated APP and TAU human genes in the brain, and closely recapitulate the human amyloid and TAU pathology [ 26 ], including cognitive deficits and the alteration in exploratory and anxiety-like behavior, fear learning and inflexibility in hippocampus-dependent learning [ 1 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer’s disease (AD) is a chronic and progressive neurodegenerative disorder, characterized by broad neurologic, cognitive, functional, behavioral and psychological impairments [ 1 , 2 ], that is considered the greatest challenge for health and social care in the 21st century, having a global impact on patients and their families, communities and society [ 3 ].…”
Section: Introductionmentioning
confidence: 99%